Hubungan Pengetahuan Diet dengan Kadar Gula Darah Pasien Diabetes Melitus Tipe 2 di Klinik Mutiara Delima - Ucik Ernawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by decreased insulin production or decreased sensitivity of body cells to insulin. As a result, blood glucose levels increase significantly and can lead to various serious complications if not properly managed. Management of T2DM requires a multidisciplinary approach, one of which is proper dietary management. A controlled diet plays a crucial role in maintaining stable blood sugar levels, preventing complications, and improving the patient's quality of life. Therefore, patient understanding of a special diabetes diet is crucial. A good understanding of dietary principles will help patients choose the right types and amounts of food to avoid triggering blood glucose spikes. Furthermore, continuous nutrition education also plays a crucial role in developing healthy eating habits in T2DM patients. This study aims to analyze the relationship between patient knowledge about diabetes diets and blood sugar control in T2DM patients. The research method used was a quantitative approach with a correlational and cross-sectional design. A total of 40 respondents were selected using consecutive sampling. The independent variable in this study was the level of knowledge of diabetes diets, while the dependent variable was blood glucose control. Data were collected through questionnaires and observation sheets. Univariate analysis was used to describe respondent characteristics, while bivariate analysis using the Spearman Rank test was used to examine the relationship between variables. The test results showed a significance value of p = 0.0002, indicating a significant relationship between dietary knowledge and blood sugar control in people with T2DM.